Alexander Bogdanov and the question of unity: An emerging research agenda. (23rd January 2023) - Şenalp, Örsan; Midgley, Gerald
Abstract: In this paper, we propose a research agenda to support the recovery of Alexander Bogdanov's philosophical and systemic thinking that culminated in his magnum opus, Tektology . Our main reason for doing so is to re‐address enduring questions about the unity of science and the unity of the systems paradigm. Since the turn of the new millennium, there has been renewed interest in the ideal of the unity of science. General system theory (GST), cybernetics and complexity science are three significant intellectual sources inspiring this renewal. It is not unusual for these ideas to be grouped under the umbrella terms systems science or systems thinking, which are two ways to present a single systems paradigm, and we will explain why its "unity" is both necessary and problematic. Bringing Bogdanov's work back to address the unity question can help us to progress toward unity in diversity.